2018
DOI: 10.22161/ijeab/3.5.50
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and antibiofilm activities of quercetin against clinical isolates of Staphyloccocus aureus and Staphylococcus saprophyticus with resistance profile

Abstract: The aim of this study was to determine the antibacterial and antibiofilm properties of quercetin against clinical isolates of Staphyloccocus aureus and Staphylococcus saprophyticus with resistance profile. The antibacterial activity of quercetin was performed by the determination of the minimum inhibitory concentration (MIC) through the microdilution method according to the Clinical and Laboratory Standards Institute (CLSI). The percentage of inhibition of Staphylococcus spp. biofilm, after treatment with sub-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…However, neither 64 μg/ml nor 128 μg/ml impaired the growth of S. aureus, which is consistent with the previous studies (Carrada and Sánchez, 2017;Wang et al, 2019). This differs from the results of Júnior et al, showing that 250-500 μg/ml QEN inhibited 50% of biofilm formation in the MRSA bacterial strains and is similar to the 50 μg/ml concentration of MSSA ATCC 6538 (Lee et al, 2013;Júnior et al, 2018). To further determine whether QEN affects the growth of the S. aureus, the cell morphology of S. aureus was observed using transmission electron microscopy, and QEN was found to trigger the sparseness of the S. aureus cell wall structure, but the division and proliferation were not affected.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…However, neither 64 μg/ml nor 128 μg/ml impaired the growth of S. aureus, which is consistent with the previous studies (Carrada and Sánchez, 2017;Wang et al, 2019). This differs from the results of Júnior et al, showing that 250-500 μg/ml QEN inhibited 50% of biofilm formation in the MRSA bacterial strains and is similar to the 50 μg/ml concentration of MSSA ATCC 6538 (Lee et al, 2013;Júnior et al, 2018). To further determine whether QEN affects the growth of the S. aureus, the cell morphology of S. aureus was observed using transmission electron microscopy, and QEN was found to trigger the sparseness of the S. aureus cell wall structure, but the division and proliferation were not affected.…”
Section: Discussionsupporting
confidence: 89%
“…Prior to determining whether QEN affected S. aureus biofilm formation, available literature revealed that the MBIC of QEN on the biofilm ranged from 9 μg/ml to 60 μg/ml (Amin et al, 2015;Júnior et al, 2018;Mohamed et al, 2020). Therefore, we established 0 μg/ml, 8 μg/ml, 16 μg/ml, 32 μg/ml, 64 μg/ml, 128 μg/ml concentrations gradient to examine their MBIC value .…”
Section: The Effect Of Quercetin On Biofilm Formation In Staphylococcus Aureusmentioning
confidence: 99%
See 1 more Smart Citation
“…The best inhibitory effect of QRC was observed against the methicillin-sensitive Staphylococcus aureus (MSSA), methicillin-resistant Staphylococcus aureus (MRSA), and vancomycin-intermediate Staphylococcus aureus (VISA) strains (MIC = 250, 500 and 125 µg/mL, respectively), while the lowest inhibitory effect was against the vancomycin-resistant Staphylococcus aureus (VRSA) strain (MIC = 1000 µg/mL). Regarding the antibiofilm activity, QRC was able to reduce 50% of the biofilm production, even when it was analysed in sub inhibitory concentrations [40].…”
Section: The Antibacterial Effect Of Quercetinmentioning
confidence: 96%
“…Quercetin is a major flavonoid content in most plant extracts ( Junior et al, 2018 ). Quercetin is found in apples, red grapes, kales, broccoli, onions, berries, and cherries ( Xu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%